2015
DOI: 10.1021/acs.biochem.5b00845
|View full text |Cite
|
Sign up to set email alerts
|

Restricting the ψ Torsion Angle Has Stereoelectronic Consequences on a Scissile Bond: An Electronic Structure Analysis

Abstract: Protein motion is intimately linked to enzymatic catalysis, yet the stereoelectronic changes that accompany different conformational states of a substrate are poorly defined. Here we investigate the relationship between conformation and stereoelectronic effects of a scissile amide bond. Structural studies have revealed that the C-terminal glycine of ubiquitin and ubiquitin-like proteins adopts a syn (ψ ~ 0°) or gauche (ψ ~ ±60°) conformation upon interacting with deubiquitinases/ubiquitin-like proteases. We us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…We finally asked the question why the unusual syn -backbone conformation of N373 with φ, ψ ≈ −180°, 0° is associated with fast deamidation. Interestingly, population in this unusual area of the Ramachandran plot has been observed before for a residue preceding a scissile bond . It seems to be linked to a special type of backbone distortion, namely, amide twisting, which is associated with a syn -backbone conformation.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…We finally asked the question why the unusual syn -backbone conformation of N373 with φ, ψ ≈ −180°, 0° is associated with fast deamidation. Interestingly, population in this unusual area of the Ramachandran plot has been observed before for a residue preceding a scissile bond . It seems to be linked to a special type of backbone distortion, namely, amide twisting, which is associated with a syn -backbone conformation.…”
Section: Discussionsupporting
confidence: 57%
“…We can profit from the highly advanced hybrid density functional theory calculations of the model tripeptide Gly−Gly−ε-Lys by Strieter and Andrew. 55 These authors found that a twisting around the (iso)peptide bond leads to a pyramidalization of the carbonyl, an increased sp 2 character, and thus higher electrophilicity, which is central to their discussed mechanism of isopeptide-bond cleavage. Interestingly, and more important for deamidation, is that peptide bond twisting leads to an even larger pyramidalization of the nitrogen, which is accompanied by rehybridization from sp 2 to sp 3 and thus generating a free electron pair at the nitrogen.…”
Section: ■ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, the Tipper-Strominger hypothesis [67], in other words, that β-lactam antibacterials mimic the conformation of the D-Ala-D-Ala component of the PBP bacterial cell wall substrate, may be relevant [68], in that in order to get to the stage where reaction to the acylenzyme complex can occur the β-lactam antibacterial must efficiently compete with the natural substrate for binding [69]. Following from biophysical evidence that some nucleophilic serine enzymes may bind their substrates in a high-energy conformation which strains the amide bond [70][71][72], a refinement of the Tipper-Strominger hypothesis suggests that (some) β-lactam antibacterials may mimic a strained conformation of the D-Ala-D-Ala entity (Figure 2) [73][74][75]. Thus, (at least some) β-lactam antibacterials may be highly optimized to bind both noncovalently and covalently; following noncovalent binding, they undergo covalent reaction to form an initial acyl-enzyme complex which at least, in some cases, can undergo either covalent fragmentation [52,53,76] or conformational rearrangement [23,52,[55][56][57]59,62,77] to form (a) more stable complexes.…”
Section: Future Science Groupmentioning
confidence: 99%